Edutainment sebagai Strategi Inovatif dalam Membangun Kemampuan Wirausaha dan Motivasi Belajar - Wahyudi, Triyono Arief (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2020)
This Community Service Program aims to develop the entrepreneurial skills of coastal communities, particularly the students of Rumah Pintar Anak Pesisir (RPAP) and traditional fishermen in Blok Eceng, Muara Angke, North Jakarta, in aquaculture and fish-based product processing. The program is designed to build capacity, willingness, and skills to manage and sustain joint business ventures, while fostering learning motivation through the edutainment method. This study employed a qualitative approach, using observation, training, discussion, and Q&A sessions as data collection instruments. The results show an increase in participants’ creativity and innovation in developing marine-based products, critical thinking abilities, problem-solving skills in addressing environmental challenges, and awareness of the importance of formal education. The program is expected to be sustained through continued entrepreneurship training, product innovation, and marketing strategies adapted to local potential.